2012
DOI: 10.1016/j.neuroscience.2012.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Transient decrease in nociceptor GRK2 expression produces long-term enhancement in inflammatory pain

Abstract: In heterozygous mice, attenuation of G-protein-coupled receptor kinase 2 (GRK2) level in nociceptors is associated with enhanced and prolonged inflammatory hyperalgesia. To further elucidate the role of GRK2 in nociceptor function we reversibly decreased GRK2 expression using intrathecal antisense oligodeoxynucleotide (AS-ODN). GRK2 AS-ODN administration led to an enhanced and prolonged hyperalgesia induced by prostaglandin E 2, epinephrine and carrageenan. Morover, this effect persisted unattenuated 2 weeks a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 52 publications
3
47
0
Order By: Relevance
“…Earlier studies by us and others have shown that Epac1 protein levels in the DRG are increased in the CFA model of chronic inflammatory pain, whereas GRK2 levels are decreased (16,17,(30)(31)(32). In addition, we presented evidence that Epac1-dependent pain signaling is inhibited by GRK2, but the mechanism remained to be determined (17).…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Earlier studies by us and others have shown that Epac1 protein levels in the DRG are increased in the CFA model of chronic inflammatory pain, whereas GRK2 levels are decreased (16,17,(30)(31)(32). In addition, we presented evidence that Epac1-dependent pain signaling is inhibited by GRK2, but the mechanism remained to be determined (17).…”
Section: Discussionmentioning
confidence: 47%
“…***P < 0.001; ****P < 0.0001. 32 P incorporation in WT-Epac1 and Epac1-S108A incubated with purified recombinant GRK2 (50 nM). (E) Rap1 activation in N2A and N2A-GRK2 (NG) cells transfected with WT-Epac1 (WT), Epac1-S108A (S108A), or Epac1-S108E (S108E) treated with 8-pCPT.…”
Section: Phosphorylation Of Epac1 At Ser-108 Inhibits Rap1 Activation Bymentioning
confidence: 99%
“…Levine and colleges found that 3 days of i.t. GRK2 AS-ODN administration produces a 39% decrease in GRK2 protein expression in the saphenous nerve (Ferrari et al , 2012), yet we observed near-ablation of GRK2 protein at the level of the DRG. The difference in knockdown suggests that the support cells adjacent to distal portions of the afferent nerve were unaffected by i.t.…”
Section: Discussionmentioning
confidence: 63%
“…Intrathecal (i.t.) injections of GRK2 AS-ODN over 3 days significantly reduced GRK2 expression in peripheral sensory nerves (Ferrari et al , 2012). Utilizing the same AS-ODN in this study, daily i.t.…”
Section: Resultsmentioning
confidence: 99%
“…Through this same regulation of p38, GRK2 exacerbates brain damage in hypoxic-ischemic injury (Nijboer et al, 2010). The importance of GRK2 in this system is highlighted in that even a transient decrease in GRK2 levels (by intrathecal injection of GRK2 antisense oligodeoxynucleotides) is sufficient to produce long-lasting neuroplastic changes in nociceptor function that can lead to chronic pain (Ferrari et al, 2012). …”
Section: Grks In Inflammatory Signaling and Diseasementioning
confidence: 99%